Analysis of turbulent diffusion flames with a hybrid fuel of methane and hydrogen in high pressure and temperature conditions using LES approach. (21st September 2015) - Hong, Sungmin; Lee, Wook; Kang, Seongwon; Song, Han Ho
Abstract In the present study, large eddy simulations (LES) of a turbulent diffusion flame with a hybrid fuel of methane and hydrogen are carried out to investigate the effects of operating conditions on the flame shape and the pollutant formation. A parametric study is performed by changing the values of hydrogen concentration and the background pressure and temperature. A flamelet-progress variable approach (FPVA) is used for a tabulated chemistry and a dynamic subgrid scale (SGS) model is used as the LES model. The result shows a good agreement with a previous experiment in the statistics of flow fields and composition. Also, the results affected by each operating parameter show consistent tendency with previous studies. Then, we investigate how the effect of added hydrogen changes for different background pressure and temperature conditions including those of a direct injection internal combustion engine. It is found that both the high compression ratio and hydrogen addition can lead to more compact and focused reaction zone by changes in the reaction and mixing rates. This also affects the pollutant formation, and the reduction of CO and NO is observed with hydrogen addition.